How Do Informal Actors Work? Between Voter Lists and Social Pressure in Elections - George Towar Ikbal Tawakkal (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2024)
Vote brokerage, as a form of brokerage activity, would have a clear and measurable commodity. Candidates will not hire vote broker when commodity can not be measured. Similarly, vote broker will not get job if there is no clear commodity that can be offered to candidate. That logic have began this study. Facts, on field indicated the debate about whether commodities (voters) actually were measured. Some brokers registered voters, and others did not, destabilizing the logic. Is vote brokerage measured and unmeasured? Do both have different measurement logic? In what did the differeneces work?. To answer these questions, I made observations and interviews in Pati at 2011-2020, where vote broker called as Sabet, and in Demak at 2015-2020, where vote broker called as Gapit. Findings, vote brokerage always measurable on two methods. Brokerage was based on list of voters name, and other was based on influence that a broker will have over voters in his respective social network. First method led to distributing money or valuable goods to voters on the list. Second method led to using social pressure to influence voters. Different type of voters made candidates assign such divergent strategies and brokerage activities to different brokers in their efforts to win elections.